2010
DOI: 10.4161/oxim.3.6.13446
|View full text |Cite
|
Sign up to set email alerts
|

A Rodent Model of Schizophrenia Reveals Increase in Creatine Kinase Activity with Associated Behavior Changes

Abstract: Schizophrenia is a debilitating mental disorder characterized by positive (delusions, hallucinations, disorganized speech) and negative (affective flattering, avolition and social withdrawal) symptoms as well as cognitive deficits. The frequency, severity and topography characterize the disorder as heterogeneous, the pathophysiology of schizophrenia is poorly understood. Sub-anesthetic doses of ketamine produce hyperactivity, stereotypy and abnormal social interaction and it is used as a model of schizophrenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Standing out amongst the pharmacological animal models of SZ are those which use the administration of non-competitive antagonists of glutamate receptors N-methyl d-aspartate (NMDA), such as ketamine (Ket) (Canever et al 2010, De Oliveira et al 2011. These are responsible for pore blockage within the NMDA channel, which prevents the influx of calcium and can induce a transient and reversible psychotic state, including the positive, negative and cognitive symptoms of SZ in healthy subjects (Mecheri et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Standing out amongst the pharmacological animal models of SZ are those which use the administration of non-competitive antagonists of glutamate receptors N-methyl d-aspartate (NMDA), such as ketamine (Ket) (Canever et al 2010, De Oliveira et al 2011. These are responsible for pore blockage within the NMDA channel, which prevents the influx of calcium and can induce a transient and reversible psychotic state, including the positive, negative and cognitive symptoms of SZ in healthy subjects (Mecheri et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A widely used animal model of schizophrenia involves the acute or repeated administration of ketamine (Becker and Grecksch 2004, Bubeníková-Valesová et al 2008, Canever et al 2010, De Oliveira et al 2011.…”
mentioning
confidence: 99%
“…The novel tank test [44] indicated that ketamine exposure can reduce anxiety of larval zebrafish in strange environment, which resembles similar results in mice [61,62]. The shoaling test [45] was designed to examine how ketamine exposure altered social behavior of zebrafish shoals.…”
Section: Functional Damage Of Ketamine In Zebrafish's Nervous Systemmentioning
confidence: 80%
“…And it has been shown that acetyl Lcarnitine's can provide protection against ketamine-induced decrease in heart rate and ERK/MAPK activity though calcium-modulated signaling [61,62]. Further studies are needed to elucidate the mechanism about how acetyl L-carnitine counteracts ketamine's adverse effects on neurons.…”
Section: Perspectivesmentioning
confidence: 99%